Wilderness in America : Philosophical Writings - Bugbee, Henry (Book collections on Project MUSE., 2017)
The purpose of this book is to remove the philosophical writings of Henry Bugbee from relative obscurity, making them more accessible to the wider public. Beginning with an introductory account of Bugbee's ""experiential naturalism, "" the development of his thought is traced from his student writings in Part One to some select published writings in Part Two, followed by heretofore unpublished writings in Part Three. Part Four consists of an in-depth interview conducted during the twilight years of his life. The book concludes with a rich collection of appendices that are intended to shed light